Mapping Research on Higher Order Thinking Skills (HOTS) in Islamic Religious Education: An R Biblioshiny Analysis - M. Nuzulul Ulum; Abdul Munip (PT. Pusmedia Group Indonesia, 2026)
This study aims to map the development of research on Higher Order Thinking Skills (HOTS) in Islamic Religious Education through bibliometric analysis using R Biblioshiny. The data were obtained from the Scopus database covering the 2015–2025 period and were selected using the PRISMA flow, resulting in 28 relevant articles. The analysis focused on publication productivity, citations, authors, institutional affiliations, keywords, and research collaboration networks. The findings indicate that publications on HOTS in Islamic Religious Education increased significantly, particularly during the 2021–2025 period, reflecting growing academic attention toward the development of higher-order thinking skills in Islamic education learning. Affiliation mapping revealed the dominance of universities in Malaysia and Indonesia as the main centers of HOTS research development. Keyword analysis showed that the studies mainly focused on active learning strategies, curriculum strengthening, and HOTS-based assessment. However, this study has several limitations, including the limited number of articles, the use of a single database, the absence of thematic map analysis, and limitations in the search keywords. Therefore, future studies are recommended to expand data sources and develop more comprehensive bibliometric analyses to provide broader and deeper insights into HOTS research in Islamic Religious Education.